Overview of Incompleteness of Filling Out Summary Forms of in- and Outpatient Medical Records on Hypertension in RSUD Lubuk Basung - Yulfa Yulia; Dian Sari; Oktamianiza; Mila Sari; Vitratul Ilahi; Kalasta Ayunda; Gopinda Deska Putra (Miracle Journal Get Press, 2024)
The admission and discharge summary is a medical record form that is used to record a summary of the course of the disease from the time the patient entered the hospital until the patient was discharged. The research used is quantitative research with a descriptive approach. Data collection was carried out at Lubuk Basung Regional Hospital from 27 May to 1 July 2023., and the sample consisted of 88 entry and exit summary forms from the medical records of patients suffering from hypertension. Research through observation with a checklist table. Computerization is used to process data and carry out univariate analysis. The results of the study showed that there were still incomplete filling out of entry and exit forms on patient identification items (40.9%), important patient reports (20.5%), patient permission (12.5%), good record keeping (15.9%) . ), and scribbled and clearly legible (17.05%). The results showed that the summary of admissions and discharges for hypertensive patients was still incomplete. In conclusion, this shows that the summary of admissions and discharges for hypertensive patients is still incomplete. It is recommended to carry out evaluations and reviews, as well as outreach and evaluation with doctors, nurses and other related personnel. It mainly deals with quantitative analysis of incoming and outgoing summaries